The relationship between breakfast habits, physical activity status and academic achievement among undergraduates in UiTM Puncak Alam Campus / Maximilia Jumi and Alia Md Yusof - Jumi, Maximilia; Md Yusof, Alia (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
A regular breakfast consumption and physical activity were among the important health practices in order to live a healthy life. However, breakfast is the most common skipped meal and physical activity has been neglected by many university students. Therefore, the present study aimed to examine the relationship between breakfast habits, physical activity and academic achievement among university students. The main objective of this study is to assess students' breakfast habit, physical activity status and their level of academic achievement. This is a cross-sectional study involving a total of 376 undergraduate students randomly selected from eight faculties in UiTM Puncak Alam Campus. A selfadministered questionnaire on breakfast habits, physical activity and academic achievement was given. There were 49.5% of the respondents classified as breakfast eaters while the other 50.5% of them were breakfast skippers. Majority of the respondents claimed to be engaged in vigorous and moderate physical activity within 1-2 days/week and they only spent 1-2 hours/day in minimal activity. Most of the respondents have moderate CGPA which ranged from 3.00-3.49. The associations of breakfast habit, physical activity and CGPA was determined by using Pearson's Chi-square test and the results obtained showed that there are no significant associations among those variables. In conclusion, the study did not find any relationship between breakfast habits, physical activity status and academic achievement.